Ubiquitous constellations: towards a non-anthropocentric anthropology - Canevacci, Massimo (MATRIZes, 2021)
The division of knowledge into disciplined-disciplines, as established by the division of labor in the industrial age, divided into faculties, departments, curricula, etc., dissolves in the air of pixels. The conceptual constellation studied is based on methodological indiscipline. Research in the material and immaterial, analog and digital fields mixes key concepts: cultural syncretisms, narrative polyphonies, ubiquitous subjectivity, restless diasporas, meta-fetishisms. The ethnographer moves around, attentive to the smallest details in the flowing landscapes; thus, learning to observe itself during the research. In the process of the reflective method, the researcher discovers part of the research and the subject/object dialectical inconsistency.